The characteristics of the ancient cell death suppressor, TMBIM6, and its related signaling pathways after endoplasmic reticulum stress. Issue 1 (1st May 2019) - Doycheva, Desislava; Kaur, Harpreet; Tang, Jiping; Zhang, John H.
Abstract: Activation of the unfolded protein response in combination with generation of reactive oxygen species, from cytochrome P450 members and NADPH‐P450 reductases, are two major consequences of Endoplasmic Reticulum (ER) stress that cause oxidative damage and cell death. Herein, we reviewed the role of Bax Inhibitor‐1 (BI‐1), an evolutionarily conserved protein encoded by the Transmembrane Bax inhibitor Motif Containing 6 gene, in protection from ER stress. As BI‐1 has multimodal properties that can target a wide array of pathophysiological consequences after injury, our main objective was to explore BI‐1's protective role in ER stress and its potential signaling pathways.